Q-EEG map of parietal and frontal lobes out of brain waves recording during dental hypnosis practice - Yubiliana, Gilang; Putra, Raka; Abdurrochman, Andri (Universitas Padjadjaran, 2021)
Introduction: A patient with fear and anxiety is a common case to deal with for a dentist, therefore, dental hypnosis has been widely used to ease this situation. In a hypnotized state, the human brain may easily accept any suggestion. This is projected in the brain waves. Electroencephalograph (EEG) is a brain wave recording device, reflecting several states of consciousness. Beta for conscious, alpha and theta for subconscious, and delta for sleep. Dental hypnosis puts down beta waves to alpha or theta. Quantitative Electroencephalography (Q-EEG) or brain mapping is a comprehensive analysis of (Electroencephalography, EEG) in a colored topographic map, reflecting the brain's electrical activity. The objective of this article was reporting the parietal and frontal lobes activity during dental hypnosis based on the Q-EEG mapping. Methods: The research applied a quantitative research method using observatory study. The sample was taken with an accidental sampling method, with inclusion criteria, patients with dental anxiety and exclusion criteria was patients with special need and high level of dental anxiety. Data of the EEG records was taken in January-March 2018, and processed after in Pramita laboratorium Bandung. Results: Parietal lobe affected more during the inducement than temporal lobe. During dental hypnosis, the hypnotic markers (theta and alpha states) observed from the EEG were found to be more reactive. Conclusion: Dental hypnosis effects can be observed easily using Quantitative Electroencephalography method. Dental hypnosis affects brainwaves and brain mapping which indicate relaxations of brain waves especially on parietal lobes.